Non-invasive risk prediction based on right ventricular function in patients with pulmonary arterial hypertension. (14th October 2021) - Qaderi, V; Weimann, J; Harbaum, L; Schrage, B; Knappe, D; Sinning, C; Schnabel, R; Blankenberg, S; Kirchhof, P; Klose, H; Magnussen, C
Abstract: Background: Individual risk assessment in patients with pulmonary arterial hypertension (PAH) is fundamental to improve their outcome. Although right ventricular (RV) dysfunction is a major determinant of outcome in PAH, echocardiographic measures of RV function are poorly represented by current risk models. Objective: The objective of this study was to identify echocardiographic measures of RV function, which are associated with adverse outcome and to develop a non-invasive, echocardiography-based risk score for PAH patients. Methods: In 254 patients with PAH we analyzed functional status, laboratory results, pulmonary function and echocardiographic measures. Echocardiographic measures comprised RV chamber diameters, right atrial area, fractional area change (FAC), tricuspid annular plane systolic excursion (TAPSE), 2D RV strain and pericardial effusion. We used Cox regression models to assess the association with the composite endpoint of 5-year all-cause death or lung transplantation. The analyses included a conventional model using only guideline-recommended variables and a model adding significant echocardiographic measures. Based on the final multivariable model a point risk score was derived, indicating the association with the primary outcome. Results: Median age was 65.5 years, 33.9% were females. During a median follow-up time of 4.18 years 74 patients died (n=63) or underwent lung transplantation (n=11). In univariable analyses low systolic blood pressure (Hazard ratio [HR] 0.99, 95% Confidence Interval [CI] 0.98, 1.00), NYHA functional class IV (HR 3.23, 95% CI 1.48, 7.07), 6-minute walk distance (HR 1.00, 95% CI 1.00, 1.00), NT-proBNP concentrations (HR 1.00, 95% CI 1.00, 1.00), renal impairment (HR 0.99, 95% CI 0.98, 1.00), reduced diffusion capacity for carbon monoxide (HR 0.99, 95% CI 0.98, 1.00), reduced TAPSE (HR 0.90, 95% CI 0.85, 0.96) and reduced FAC (HR 0.97, 95% CI 0.94, 1.00) were associated with the endpoint. A multivariable, conventional risk model, including NYHA functional class, 6-minute walk distance, NT-proBNP concentrations, pericardial effusion and right atrial area, resulted in a C-Index of 0.539. Adding TAPSE and FAC to this model improved the performance significantly (C-index 0.639, p-value 0.017). This model was translated to a 12-point score with the highest weighting assigned to TAPSE, FAC, pericardial effusion and 6-minute walk distance (Figure). Conclusion: An easily applicable score integrating non-invasive, echocardiographic parameters of RV function improves prediction of adverse outcome in PAH patients. Funding Acknowledgement: Type of funding sources: None.